Azoxystrobin hides the respiratory failure of low dose sulfoxaflor in bumble bees - Margret Jürison; Kaarel Pent; Risto Raimets; Sigmar Naudi; Marika Mänd; Reet Karise (Ecotoxicology and Environmental Safety)
Pollinators are exposed to multiple pesticides during their lifetime. Various pesticides are used in agriculture and thus not all mixtures have been tested against each other and little is known about them. In this article, we investigate the impact of sulfoxaflor, a novel sulfoximine insecticide, and azoxystrobin, a widely used strobilurin fungicide, on bumble bee Bombus terrestris worker survival and physiological functions. The dosages used in this experiment are selected from dose response experiments based on LD50 data. Due to variable interactive effects on survival, our findings reveal distinct effects on bumble bee metabolic rate and respiratory patterns induced by sulfoxaflor in combination with azoxystrobin, shedding light on previously unexplored aspects of its physiological impact. Notably, we observed noteworthy differences between oral and contact treatments, emphasizing the importance of considering distinct application methods when evaluating pesticide effects and interactions. Specifically, our results indicate that azoxystrobin can mitigate the impact of sulfoxaflor, suggesting dose-dependent antagonistic interaction between these pesticides in contact exposure. In oral exposure, however, Amistar tended to potentiate the sulfoxaflor effect. This study contributes valuable insights into the multifaceted dynamics of pesticide exposure and interactions, paving the way for a more nuanced understanding of their implications on pollinator health.